The Effect of CYP3A4, CYP3A5 and ABCB1 Polymorphisms on Tacrolimus Dose Requirements in Adult Kidney Transplant Patients - Khusnul Khotimah; Lolita; Lalu Muhammad Irham (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: Polymorphisms in the CYP3A4, CYP3A5, and ABCB1 genes play a significant role in the response to tacrolimus therapy in kidney transplant patients. Tacrolimus, a commonly used immunosuppressant, has a narrow therapeutic index and is highly influenced by individual genetic variation. These genetic polymorphisms significantly affect the response to tacrolimus therapy in patients undergoing kidney transplantation. Inaccurate dosing can lead to serious consequences: a tacrolimus dose that is too low increases the risk of acute rejection, while a dose that is too high can cause nephrotoxicity and other serious side effects. Therefore, accurate initial dosing of tacrolimus is critical in the clinical practice of kidney transplantation.. Methods: The article search was conducted using the CrossRef database, which provided access to various scientific journals. The focus was on research published in the last five years, ensuring that only studies exploring polymorphisms related to the CYP3A4, CYP3A5, and ABCB1 genes in the context of tacrolimus were used. Results: Previous analysis revealed that CYP3A5 polymorphisms were the most consistent genetic factors influencing tacrolimus metabolism; expressors with the *1/*1 and *1/*3 genotypes required higher doses to reach target levels, while non-expressors with the *3/*3 genotypes experienced a greater risk of toxicity with elevated trough levels, although contributions from CYP3A4 and ABCB1 varied based on ethnicity and transplantation stage. Conclusions: From the results of this review, it can be concluded that CYP3A5 gene polymorphisms are the primary predictors of tacrolimus dose requirements. Recommendations for implementing CYP3A5 genotyping before transplantation may enhance the efficacy of immunosuppression and reduce the risk of toxicity. Further research is necessary to develop more adaptive, pharmacogenetic-based dosing models and to evaluate the clinical factors influencing tacrolimus pharmacokinetics.